Micro-FTIR and EPMA Characterisation of Charoite from Murun Massif (Russia) - Maria Lacalamita (Journal of Spectroscopy)
Combined micro-Fourier transform infrared (micro-FTIR) and electron probe microanalyses (EPMA) were performed on a single crystal of charoite from Murun Massif (Russia) in order to get a deeper insight into the vibrational features of crystals with complex structure and chemistry. The micro-FTIR study of a single crystal of charoite was collected in the 6000–400 cm−1 at room temperature and after heating at 100°C. The structural complexity of this mineral is reflected by its infrared spectrum. The analysis revealed a prominent absorption in the OH stretching region as a consequence of band overlapping due to a combination of H2O and OH stretching vibrations. Several overtones of the O-H and Si-O stretching vibration bands were observed at about 4440 and 4080 cm−1 such as absorption possibly due to the organic matter at about 3000–2800 cm−1. No significant change due to the loss of adsorbed water was observed in the spectrum obtained after heating. The occurrence of well-resolved water bending vibration bands at about 1595 and 1667 cm−1 accounts for more than one structural water molecule as expected by charoite-90 polytype structure model from literature. The chemical composition of the studied crystal is close to the literature one.